Surface Water and Groundwater Resources Allocation for Agricultural and Environmental Purposes in Khanmirza Watershed - Khodayar Abdollahi; Sara Mardanian; Rafaat Zare Bidaki; Abuzar Salehi (مهندسی منابع آب, 2022)
AbstractIntroduction: Due to rapid expansion of population, there is an increase in the number of water users. As a result, optimal water allocation has become a pivotal issue. System dynamics is a suit methodology for simulating and representing of water availability in complex condition and impacts of water resources usage over time. In this study, a dynamic water allocation model within Vensim GUI was developed for the agricultural and environmental water resources of Khamiriza catchment.Methods: The model consists of two separate sections; the first part is a water balance module which is designed to provide surface water and groundwater simulations; the other part is a water allocation sub-model. After the development of the model, the water balance simulation optimized by optimizing the surface water and groundwater against observed data.Findings: The water use policy includes the conjunctive use of groundwater and surface water to meet drinking, industrial, agricultural, and environmental demands. The results suggest that under current situation the quantity of available surface and groundwater could be insufficient to meet the demands of different sectors within the basin. Therefore, a scenario containing improved irrigation efficiency and 30% of the land in fallow may lead to the allocation vulnerability.Conclusion:The results of this application indicate that system dynamics can be considered as an innovative tool in the planning and allocating water resources. Moreover, conjunctive use of groundwater and surface water resources may lead to a better water allocation policy.